Thomas Aquinas on seeing God: the beatific vision in his Commentary on Peter Lombard's Sentences IV.49.2 - Thomas, von Aquin, Heiliger (Mediaeval philosophical texts in translation, 2020)
"Thomas Aquinas's first eschatological account of the beatific vision 'face-to-face', as presented in his commentary on Peter Lombard's Sentences, integrates the theological discourse of his times with newly available philosophical reasoning. This book provides a translation of book 4, distinction 49, question 2 of his commentary, and comprehensively examines, in the introductions and notes, how Aquinas solved the deepest conceptual dilemmas of his predecessors"--